Laser-written high-temperature resistant nano-copper and its preparation method and application
High-temperature resistant nanocopper is prepared through laser direct write-induced passivation/photothermal reduction and sintering method, which solves the problem of oxidation failure of nanocopper under high temperature conditions and realizes its efficient application in the fields of conductive electrodes, transistors, sensors and electrochemical batteries.
Patent Information
- Application Number
- CN202410615775.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-17
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2044-05-17
AI Technical Summary
In the prior art, nanocopper is prone to oxidation under high temperature conditions, resulting in deterioration of conductivity, limiting its application in the fields of conductive electrodes, transistors, sensors, and electrochemical batteries.
High-temperature resistant nanocopper is prepared by laser direct write-induced passivation/photothermal reduction and sintering method. Formate passivation on the nanocopper surface is induced by laser high-energy radiation to form a stable antioxidant coordination passivation layer to improve its oxidation resistance and thermal stability.
The good oxidation resistance and thermal stability of nanocopper at high temperatures are achieved, while maintaining excellent conductivity, solving the problem of oxidation failure of nanocopper at high temperatures.
Smart Images

Figure CN118437937B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of preparation of nano copper, and in particular relates to high temperature resistant nano copper directly written by laser, and a preparation method and application thereof. Background Art
[0002] Copper, as a metal widely used in human society, plays an important role in the fields of construction, electricity, communication, energy, and medical treatment with its unique properties and advantages. Among them, nano copper has become a promising material in functional electronic fields such as conductive electrodes, transistors, sensors, and electrochemical cells due to its good electrical / thermal properties and economic benefits. However, copper is very easy to oxidize under high temperature conditions, causing the deterioration of metal properties and conductivity degradation, which greatly limits its application. Compared with bulk copper, nano copper has a high specific surface area and is more likely to react with oxygen. Therefore, the oxidation failure problem of nano copper is much more serious than that of bulk copper.
[0003] In order to improve the high temperature oxidation resistance and thermal stability of nano copper, a variety of antioxidant treatment methods have been developed:
[0004] (1) Surface coating: By coating a layer of inert material (such as graphene, graphene oxide, gold / silver / platinum and other precious metals) on the surface of nano-copper, oxygen can be effectively blocked from direct contact with nano-copper.
[0005] (2) Surface modification: Through surface adsorption or chemical bonding of some organic molecules / polymers, etc., they react with nano-copper to form stable compounds to slow down its oxidation rate at high temperatures.
[0006] (3) Alloying: Nano copper is compounded with other metals (such as nickel, tin, aluminum, manganese, etc.) to form an alloy to increase the melting point of nano copper, thereby improving its antioxidant properties at high temperatures.
[0007] (4) Atmosphere control: During the sintering or high-temperature treatment of nano-copper, oxidation can be effectively prevented by controlling the processing atmosphere (such as inert / reducing gas protection, vacuum conditions).
[0008] Among the above treatment methods, methods (1) and (2) have more significant high-temperature antioxidant effects, but the cost is high, the process flow is more complicated, and it will affect the electrothermal properties of nano copper to a certain extent. Although method (3) can improve the antioxidant property, it will also change other physical and chemical properties of nano copper, resulting in it no longer meeting the original application requirements. Method (4) is mainly suitable for specific treatment environments, and it is difficult to maintain it for a long time in actual applications. It also requires expensive equipment support, which increases the complexity and cost of the operation.
[0009] In the prior art, the corresponding method (1) is to take the patent number CN202111501706.2, "A method for preparing an oxidation-resistant copper-based surface-enhanced Raman scattering substrate", as an example. A nanoporous copper strip with a double continuous structure is prepared by stripping and dealloying; then the nanoporous copper is pickled to remove the surface oxide layer; finally, a graphene oxide solution is spin-coated on the surface of the nanoporous copper, and then immediately transferred to a tubular furnace for thermal reduction under a hydrogen and argon atmosphere to obtain a nanoporous copper coated with an ultra-thin reduced graphene oxide layer, so as to further slow down its oxidation, thereby ensuring the stability of the reduced graphene oxide / nanoporous copper composite substrate in Raman detection. Although the invention has good stability and high repeatability, the process steps are cumbersome and need to be carried out in an inert gas, and the reaction conditions are relatively harsh.
[0010] In the prior art, the corresponding method (1) is described in the patent number CN201710343566.8, "A novel anti-oxidation nano-copper solder paste and its preparation method and application". The metal film (gold or silver) is uniformly coated on the surface of nano-copper powder by magnetron sputtering process, and then the traditional nano-copper solder paste formula is used, and an appropriate amount of molding aid is added to finally prepare a novel anti-oxidation and anti-cracking anti-oxidation nano-copper solder paste. This invention avoids the oxidation of nano-copper by coating the inert metal gold / silver layer, and can serve for a long time without trouble at high temperature. However, it significantly increases the material cost and limits large-scale application.
[0011] In the prior art, corresponding to method (2), taking the patent number CN201710752263.1 "A method for preparing anti-oxidative copper nanowires" as an example, firstly, copper nanowires are added to a dispersant, and polar organic solvents and / or water are added, and mixed to obtain a copper nanowire dispersion; then an antioxidant is added to the copper nanowire dispersion and mixed to obtain a mixed solution; then the mixed solution is placed in a pressurized and heated sealed system for reaction; finally, the mixed solution is cooled, and after liquid-solid separation and washing, the copper nanowires with anti-oxidative surface treatment are obtained, namely, the anti-oxidative copper nanowires. This invention is simple to operate and low in cost, but the operation process is relatively cumbersome, the reaction time is long, and a pressurized and heated closed reaction condition is required, which is not suitable for efficient processing under room temperature.
[0012] In the prior art, corresponding to method (2), taking "Anti-oxidation copper film / copper wire and its preparation method and application" with patent number CN202110912124.7 as an example, anti-oxidation copper powder, alcohol solvent, amine solvent, resin, and additive are ground and mixed, and degassed to obtain an anti-oxidation copper slurry; the anti-oxidation copper slurry is coated on a substrate, dried and pre-cured under an inert atmosphere to obtain a copper film precursor 1 / copper wire precursor 1; the copper film precursor 1 / copper wire precursor 1 is cured under an inert atmosphere to obtain a copper film precursor 2 / copper wire precursor 2; the copper film precursor 2 / copper wire precursor 2 is placed in a compound containing a thiol group or a disulfide bond to obtain an anti-oxidation copper film / copper wire. Although the copper film / copper wire obtained by the invention has excellent oxidation resistance, an inert atmosphere is required to obtain high conductivity, and the preparation conditions are relatively harsh.
[0013] In the prior art, corresponding to method (3), taking the patent number CN201410532942.4 "A method for preparing copper-nickel alloy nanoparticles" as an example, prepare a mixture of copper nitrate trihydrate and nickel nitrate hexahydrate, and stir and add a ligand and a dispersant (the molar ratio of copper nitrate to ligand is 1:0.5-1:4, and the molar ratio of copper nitrate to dispersant is 1:1-1:2); place the above solution in a drying oven at 160-180°C and dry it to a porous dry gel without moisture; in an argon atmosphere, calcine the dry gel at 500-700°C for 2-5h, thereby obtaining copper-nickel alloy nanoparticles. This invention has the advantages of easy availability of raw materials and high yield, but the preparation process involves a high temperature environment and an inert atmosphere, which to a certain extent limits its wide-range application.
[0014] In the prior art, the corresponding method (3) is taken as an example of "a nano copper-tin alloy conductive ink and its preparation method and use method" with patent number CN201110055004.6. Nano copper-tin alloy is used instead of nano copper-silver alloy as the conductive filler in the conductive ink, which not only reduces the sintering temperature of the conductive ink, but also improves the anti-oxidation ability during sintering and the mechanical properties and solderability of the conductive circuit formed after sintering compared with the nano copper-silver alloy conductive ink, and avoids the problem of silver ion migration. In addition, the nano copper-tin alloy is doped with rare earth metal elements, which increases its grain boundaries, increases the electron scattering rate, and increases the conductivity compared with the nano copper alloy. On the other hand, it also reduces the raw material cost of the conductive ink. However, the addition of tin element reduces the melting point of the nano copper-tin alloy, which is not conducive to the anti-oxidation property in a long-term high temperature environment.
[0015] In the prior art, the corresponding method (4) is to take the "A method for preparing an anti-oxidation micro-nano copper material" with patent number CN201910399914.2 as an example, using a micro-nano copper preparation device to prepare micro-nano copper powder; placing an organic coating agent in the vacuum chamber of the in-situ coating device, and sublimating or vaporizing the organic coating agent in the vacuum chamber by heating; introducing an inert gas into the preparation system, and the micro-nano copper powder is introduced into the vacuum chamber of the in-situ coating device along with the inert gas, and the sublimated or vaporized organic coating agent contacts and is coated on the surface of the micro-nano copper particles. Although the vacuum heating and inert atmosphere in the invention form a good organic coating on the surface of the micro-nano copper ions, greatly improving the anti-oxidation and dispersibility of the micro-nano copper particles and reducing their surface activity, the specific processing environment of the whole process is bound to greatly increase the cost, which does not meet the actual application requirements.
[0016] In the prior art, the corresponding method (4) is taken as an example of "a kind of anti-oxidation super-hydrophobic copper film and its preparation method" with patent number CN202111250495.X. The copper nanoclusters produced after the decomposition of the organometallic precursor are used as catalysts to catalyze the decomposition of the liquid organic precursor into graphite carbon, which is enriched on the surface of the copper nanoclusters to form the grains of the copper-carbon core-shell structure, and countless copper-carbon grains are deposited on the substrate surface to form an anti-oxidation super-hydrophobic copper film. The invention mainly uses chemical vapor deposition to form an anti-oxidation copper-carbon film on the substrate surface, and the relatively rough nanostructure surface formed by deposition is used to obtain super-hydrophobic properties, which is convenient for overall control and has good repeatability, but it is still impossible to avoid the harsh reaction conditions (needing hydrogen and argon inert atmosphere control, 400-600°C reaction temperature, 1000-9000Pa reaction pressure), which will inevitably cause cost-effectiveness problems.
[0017] Therefore, developing an antioxidant surface treatment method for high-temperature resistant nano-copper that is simple to prepare, efficient to process, highly compatible, and cost-effective is a current technical challenge in solving the application of nano-copper in functional electronic fields such as conductive electrodes, transistors, sensors, and electrochemical cells. Summary of the invention
[0018] The purpose of the present invention is to provide a laser-written high-temperature resistant nano-copper and a preparation method and application thereof in view of the deficiencies in the prior art. The high-temperature resistant nano-copper is prepared by laser direct writing induction.
[0019] The preparation method of high temperature resistant nano copper by laser direct writing in the present invention mainly comprises the following steps:
[0020] (1) uniformly heating and stirring an alcohol solvent, an organic dispersant, an organic auxiliary agent, and an appropriate amount of formate to obtain a precursor solution;
[0021] (2) adding an appropriate amount of nano copper oxide to the precursor solution and fully dispersing it by ultrasonication to obtain nano copper oxide ink;
[0022] (3) coating the nano copper oxide ink on the pretreated substrate, heating and drying, to obtain a nano copper oxide film;
[0023] (4) The nano copper oxide film is subjected to laser direct writing induced passivation / photothermal reduction sintering to obtain high temperature resistant nano copper.
[0024] The alcohol solvent in step (1) is selected from at least one of monohydric alcohol, dihydric alcohol and polyhydric alcohol; the organic dispersant is selected from at least one of polyacrylamide organic polymer, polyethylene oxide organic polymer, tannin and lignin, but is not limited thereto; the organic auxiliary agent is an organic amide, and the organic amide is selected from a compound having a chemical formula conforming to C n H 2n+1 The method comprises the following steps: the step of heating and stirring the mixture: the step of heating and stirring the mixture: at least one of an alkyl amide of NO (1≤n≤5); the step of heating and stirring the mixture is selected from at least one of lithium formate, beryllium formate, sodium formate, magnesium formate, potassium formate, calcium formate, iron formate, manganese formate, cobalt formate, nickel formate, copper formate, zinc formate, barium formate and ammonium formate; the heating and stirring step is performed at a temperature of 50 to 70°C, a rotation speed of 600 to 1500 rpm and a time of 2 to 20 hours.
[0025] The nano copper oxide in step (2) is selected from at least one of copper oxide nanoparticles, copper oxide nanowires, copper oxide nanosheets, copper oxide nanorods, and copper oxide nanoshuttles; the real-time temperature of the ultrasonic dispersion is 50-60° C., the ultrasonic pulse width is 0.1 s, and the ultrasonic time is 0.1-2 h; in addition, the ultrasonic dispersion can be achieved by adding nano copper oxide in small amounts multiple times to prevent the addition of all nano copper oxide to the precursor solution and direct ultrasonic treatment, which will lead to serious agglomeration of copper oxide nanowires and poor dispersibility, and make it impossible to achieve subsequent good laser induced direct writing; the nano copper oxide ink comprises 43.0-50.4 wt% nano copper oxide, 37.1-50.4 wt% alcohol solvent, 3.4-5.3 wt% organic dispersant, 0.0-9.5 wt% organic additive, and 1.3-2.0 wt% formate; the nano copper oxide ink can be stored for a long time without being affected by oxidation, and is suitable for various manufacturing processes such as printing, coating, and printing.
[0026] The coating method described in step (3) is selected from at least one of spin coating, spraying, scraping, brushing, dripping, and screen printing, but is not limited thereto; the pretreatment is oxygen plasma surface treatment, and the treatment time is 60s to 150s; the substrate includes a flexible substrate and a rigid substrate, the flexible substrate is selected from at least one of polyimide (PI), polyethylene terephthalate (PET), polyvinyl alcohol (PVA), and polyethylene naphthalate (PEN), but is not limited thereto; the rigid substrate is selected from at least one of polyetheretherketone (PEEK), polyphenylene sulfide (PPS), polysulfone (PSF), liquid crystal polymer (LCP), glass, silicon wafer, and ceramic, but is not limited thereto; the heating and drying temperature is 50 to 80°C, and the time is 2 to 12h.
[0027] The laser in step (4) is a continuous green light with a wavelength of 532nm, the power of the laser direct writing induced passivation / photothermal reduction sintering is 100-400mW, the speed is 20-200mm / s, and the scanning period is 20-40μm.
[0028] The high temperature resistant nano copper surface has good oxidation resistance and thermal stability after being passivated by formate induced by laser direct writing, and also has excellent electrical conductivity.
[0029] The present invention also provides a full laser in-situ direct writing integrated sensor system, including a special engineering plastic substrate, a high temperature resistant nano copper interconnection circuit, a laser induced graphene temperature sensor, a voltage divider, an analog-to-digital converter (ADC), a microcontroller (MCU) and a low voltage drop linear regulator (LDO). The high temperature resistant nano copper interconnection circuit is used to connect the remaining parts to realize the integrated sensor function, wherein the high temperature resistant nano copper interconnection circuit and the laser induced graphene temperature sensor are formed in situ on the special engineering plastic substrate using full laser direct writing technology (laser direct writing induced passivation / photothermal reduction sintering and laser induced carbonization), and the high temperature resistant nano copper is prepared by any of the above-mentioned preparation methods of high temperature resistant nano copper. The special engineering plastic substrate is usually one or more of polyimide (PI), polyetheretherketone (PEEK), polyphenylene sulfide (PPS), polysulfone (PSF), and liquid crystal polymer (LCP); in particular, polyetheretherketone (PEEK) and polyphenylene sulfide (PPS) are preferred, which can be more conducive to its wide application in aerospace, automobile, electronics and other fields.
[0030] Laser direct writing induced passivation based on laser processing refers to inducing the passivation reaction of formate on the surface of nano-copper by high-energy laser irradiation, so that the copper ions on the surface of nano-copper and formate form a copper formate dimer complex, forming a stable and effective antioxidant coordination passivation layer, thereby improving the surface properties of nano-copper, greatly improving its antioxidant and thermal stability, and obtaining a high-temperature resistant nano-copper. In the present invention, laser direct writing induced passivation has the following advantages:
[0031] (1) Efficient processing: The laser direct writing induced passivation process is extremely rapid, and it can focus high-intensity energy and form a reaction temperature field in a short time to complete the formate passivation of the nano copper surface. Compared with traditional chemical passivation or physical plating methods, laser direct writing induced passivation greatly shortens the production cycle and improves processing efficiency.
[0032] (2) Patterning control: Laser direct writing induced passivation can precisely control the processing area. Its typical patterning capability allows local passivation of the nano-copper surface, thereby achieving targeted improvement of the high-temperature antioxidant properties of specific areas of nano-copper.
[0033] (3) No additional treatment is required: Laser direct writing induced passivation does not rely on pre-treatment, post-treatment, and external chemical reagents. It can be carried out directly in the atmospheric environment without the need for harsh reaction conditions such as vacuum or inert atmosphere. The treatment process is simple and greatly reduces manufacturing costs. It is an environmentally friendly anti-oxidation surface treatment method.
[0034] (4) Multi-performance integration: Laser direct writing induced passivation reduces and sinters copper oxide nanoparticles into nano-copper through a one-step direct writing process, while improving the oxidation resistance of nano-copper, enhancing its thermal stability in high temperature environments, and making nano-copper have excellent conductivity.
[0035] (5) Strong compatibility: Laser direct writing induced passivation is not limited by the shape and complexity of nano-copper materials and is suitable for multi-scale nano-copper. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 is an optical photograph of the prepared precursor solution;
[0037] Figure 2 This is an optical photograph of the prepared nano copper oxide ink;
[0038] Figure 3 This is an optical photograph of the prepared serpentine pattern high temperature resistant nano copper electrode;
[0039] Figure 4 The relative resistance changes of nano copper with different sodium formate concentrations heated at 170℃ for different time in dry air atmosphere;
[0040] Figure 5The resistance change of nano-copper after laser surface treatment at different copper oxide nanowire concentrations;
[0041] Figure 6 This is the optical image of nano-copper when the laser power is 250mW;
[0042] Figure 7 This is the optical image of nano-copper when the laser power is 100mW;
[0043] Figure 8 This is the optical image of nano-copper when the laser power is 400mW;
[0044] Fig. 9 The resistance change of nano copper after surface treatment with different laser powers;
[0045] Fig.10 The relative resistance change of nano copper after surface treatment with different laser powers at 80°C over time;
[0046] Fig.11 This is the optical image of nano-copper when the laser line scanning period is 15μm;
[0047] Fig.12 This is the optical image of nano-copper when the laser line scanning period is 45μm;
[0048] Fig.13 The resistance change of nano copper after surface treatment at different laser line scanning cycles;
[0049] Fig.14 The relative resistance change of nano copper after being treated with different laser line scanning cycles at 170°C over time;
[0050] Fig.15 The relative resistance changes of nano copper (LIP-Cu) and nano copper (Cu) without sodium formate at 170°C over time;
[0051] Fig.16 The relative resistance changes of nano copper (LIP-Cu) and nano copper (Cu) without sodium formate at 120°C over time;
[0052] Fig.17 The relative resistance changes of nano copper (LIP-Cu) and nano copper (Cu) without sodium formate when the temperature gradually increases from 30℃ to 170℃;
[0053] Fig.18 Optical photograph of the all-laser in-situ direct writing integrated sensor system. DETAILED DESCRIPTION
[0054] The present invention is described in detail below by way of embodiments in combination with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and are therefore only used as examples, and cannot be used to limit the protection scope of the present invention.
[0055] The first aspect of the present invention provides a method for preparing high temperature resistant nano copper by laser direct writing, which mainly comprises the following steps:
[0056] (1) uniformly heating and stirring an alcohol solvent, an organic dispersant, an organic auxiliary agent, and an appropriate amount of formate to obtain a precursor solution;
[0057] (2) adding an appropriate amount of nano copper oxide to the precursor solution and fully dispersing it by ultrasonication to obtain nano copper oxide ink;
[0058] (3) coating the nano copper oxide ink on the pretreated substrate, heating and drying, to obtain a nano copper oxide film;
[0059] (4) The nano copper oxide film is subjected to laser direct writing induced passivation / photothermal reduction sintering to obtain high temperature resistant nano copper.
[0060] Embodiment 1:
[0061] S1: Weigh 0.5 g of polyvinyl pyrrolidone and 0.15 g of sodium formate, mix them in 3.0 mL of ethylene glycol, and heat and stir them uniformly at 60 °C and 1200 rpm for 6 h to obtain a precursor solution;
[0062] S2: Weigh 1.5 g of copper oxide nanowires (40 nm) and place them in the precursor solution for full ultrasonic dispersion. The ultrasonic real-time temperature is 55° C., the ultrasonic pulse width is 0.1 s, and the ultrasonic time is 2 min to obtain a nano copper oxide solution 1;
[0063] S3: Weigh 1.5 g of copper oxide nanowires (40 nm) and place them in nano copper oxide solution 1 for full ultrasonic dispersion. The ultrasonic real-time temperature is 55° C., the ultrasonic pulse width is 0.1 s, and the ultrasonic time is 2 min to obtain nano copper oxide solution 2;
[0064] S4: Weigh 2.0 g of copper oxide nanowires (40 nm) and place them in the nano copper oxide solution 2 for full ultrasonic dispersion. The ultrasonic real-time temperature is 55° C., the ultrasonic pulse width is 0.1 s, and the ultrasonic time is 3 min to obtain nano copper oxide ink;
[0065] S5: Mechanically shake the nano copper oxide ink for 1 min and let it stand for later use;
[0066] S6: Take a polyphenylene sulfide special engineering plastic substrate with a thickness of 2 mm and a size of 20×50 mm, wash the surface impurities with isopropyl alcohol ultrasonic for 5 minutes, and dry it for later use;
[0067] S7: subjecting the polyphenylene sulfide special engineering plastic substrate to oxygen plasma surface treatment for 120 seconds;
[0068] S8: Vacuum adsorb the polyphenylene sulfide special engineering plastic substrate on the spin coating chuck of the spin coater, and drop 1.5 mL of nano copper oxide ink at the center of the substrate, and spin coat at 1000 rpm for 20 s and 500 rpm for 10 s;
[0069] S9: placing the polyphenylene sulfide special engineering plastic substrate after spin coating the nano copper oxide ink in a constant temperature blast drying oven or a vacuum drying oven for heating and drying at a temperature of 60° C. for 2 h to obtain a nano copper oxide film;
[0070] S10: placing a polyphenylene sulfide special engineering plastic substrate covered with a nano copper oxide film on a laser processing platform with a continuous green light of 532 nm wavelength, and adjusting the height of the processing platform for laser focusing;
[0071] S11: Draw a serpentine electrode pattern with a size of 18.0×15.3 mm, so that the laser performs pattern direct writing (laser direct writing induced passivation / photothermal reduction sintering) along the serpentine electrode pattern filling path with a power of 250 mW, a speed of 40 mm / s, and a line scanning period of 30 μm, and converts the black nano-copper oxide at the scanning path into red nano-copper to obtain a high-temperature resistant nano-copper electrode.
[0072] Figure 1 This is an optical photograph of the prepared precursor solution.
[0073] Figure 2 This is an optical photograph of the prepared nano copper oxide ink.
[0074] Figure 3 This is an optical photograph of the prepared serpentine pattern high-temperature resistant nano-copper electrode.
[0075] Embodiment 2:
[0076] S1: Weigh 0.5 g of polyvinyl pyrrolidone and 0.05 g / 0.10 g / 0.15 g / 0.20 g / 0.25 g of sodium formate in sequence, mix them in 3.0 mL of ethylene glycol and 1.0 mL of N,N-dimethylformamide solution, and heat and stir uniformly at 60 °C and 1200 rpm for 12 h to obtain 5 precursor solutions with different sodium formate concentrations;
[0077] S2: Weigh 2.0 g of copper oxide nanowires (40 nm) respectively and place them in 5 precursor solutions for full ultrasonic dispersion. The ultrasonic real-time temperature is 55° C., the ultrasonic pulse width is 0.1 s, and the ultrasonic time is 3 min to obtain 5 kinds of nano copper oxide solutions 1;
[0078] S3: Weigh 2.0 g of copper oxide nanowires (40 nm) respectively and place them in 5 kinds of nano copper oxide solutions 1 for full ultrasonic dispersion, with the ultrasonic real-time temperature being 55° C., the ultrasonic pulse width being 0.1 s, and the ultrasonic time being 3 min, to obtain 5 kinds of nano copper oxide solutions 2;
[0079] S4: Weigh 1.0 g of copper oxide nanowires (40 nm) and place them in 5 kinds of nano copper oxide solutions 2 for full ultrasonic dispersion. The ultrasonic real-time temperature is 55° C., the ultrasonic pulse width is 0.1 s, and the ultrasonic time is 2 min to obtain 5 kinds of nano copper oxide inks;
[0080] S5: Mechanically shake the nano copper oxide ink for 2 minutes and let it stand for later use;
[0081] S6: Take 5 pieces of polyphenylene sulfide special engineering plastic substrates with a thickness of 2 mm and a size of 20×50 mm, wash the surface impurities with isopropyl alcohol ultrasonic for 5 minutes, and dry them for later use;
[0082] S7: subjecting the polyphenylene sulfide special engineering plastic substrate to oxygen plasma surface treatment for 120 seconds;
[0083] S8: vacuum adsorb the polyphenylene sulfide special engineering plastic substrate on the spin coating chuck of the spin coater in turn, and drop 1.5 mL of nano copper oxide ink with different sodium formate concentrations at the center of the substrate, and spin coat at 1000 rpm for 20 s and 500 rpm for 10 s;
[0084] S9: placing the polyphenylene sulfide special engineering plastic substrate after spin coating the nano copper oxide ink in a constant temperature blast drying oven or a vacuum drying oven for heating and drying at a temperature of 60° C. for 5 hours to obtain a nano copper oxide film;
[0085] S10: placing a polyphenylene sulfide special engineering plastic substrate covered with a nano copper oxide film on a laser processing platform with a 532nm wavelength continuous green light, and adjusting the height of the processing platform for laser focusing;
[0086] S11: Draw a rectangular electrode pattern with a size of 36×6 mm, so that the laser performs pattern direct writing (laser direct writing induced passivation / photothermal reduction sintering) along the rectangular electrode pattern filling path in sequence at a power of 250 mW, a speed of 40 mm / s, and a line scanning period of 35 μm, and converts the black nano copper oxide at the scanning path into red nano copper to obtain a nano copper electrode;
[0087] S12: Manually apply a thin silver paste on both ends of each nano copper electrode to draw out the electrode, and place it in a vacuum drying oven for heating and drying at a temperature of 60° C. for 4 hours;
[0088] S13: designing a voltage divider circuit board according to the resistance value of the nano copper electrode, and connecting each nano copper electrode in turn through an alligator clip wire, and connecting to a data acquisition instrument through a Dupont line;
[0089] S14: placing the nano copper electrode in a constant temperature blast drying oven, setting the temperature to 170° C., and recording the partial pressure change in real time through a data acquisition instrument;
[0090] S15: Convert the data results into relative resistance changes of the nano copper electrode through a voltage division formula.
[0091] Figure 4 The relative resistance change of nano-copper with different sodium formate concentrations at 170°C over time. It can be seen that when the sodium formate content is 0.15g, its high-temperature resistance after laser direct writing induced passivation is the best. When the sodium formate content decreases, the complex formed by its coordination with the surface of nano-copper is not enough to resist oxygen invasion, and the high-temperature oxidation resistance is poor. When the sodium formate content increases, it will trigger additional reactions between the nano-copper interfaces, affecting the passivation effect and surface properties, and will cause the high-temperature oxidation resistance of nano-copper to fail in the long run.
[0092] Embodiment 3:
[0093] S1: Weigh 0.5 g of polyvinyl pyrrolidone and 0.15 g of sodium formate, mix them in 3.0 mL of ethylene glycol and 3.0 mL of isopropanol, and heat and stir uniformly at 60 ° C and 1200 rpm for 6 h to obtain a precursor solution;
[0094] S2: Weigh 2.0g / 3.0g / 4.0g / 5.0g / 6.0g / 7.0g of copper oxide nanowires (40nm) in sequence, place them in the precursor solution in small amounts and multiple times for full ultrasonic dispersion, with the ultrasonic real-time temperature being 55°C, the ultrasonic pulse width being 0.1s, and the single ultrasonic time being 2min, to obtain nano copper oxide inks with different copper oxide nanowire concentrations;
[0095] S3: Mechanically shake the nano copper oxide ink for 1 to 3 minutes and let it stand for later use;
[0096] S4: Take 6 pieces of polyphenylene sulfide special engineering plastic substrates with a thickness of 2 mm and a size of 20×50 mm, wash the surface impurities with isopropyl alcohol ultrasonic for 5 minutes, and dry them for later use;
[0097] S5 is the same as S7 in Example 2;
[0098] S6: vacuum adsorb the polyphenylene sulfide special engineering plastic substrate on the spin coating chuck of the spin coater in turn, and drop 1.5 mL of nano copper oxide ink with different copper oxide nanowire concentrations at the center of the substrate, and spin coat at 1000 rpm for 20 s and 500 rpm for 10 s;
[0099] S7: placing the polyphenylene sulfide special engineering plastic after spin coating the nano copper oxide ink in a constant temperature blast drying oven or a vacuum drying oven for heating and drying at a temperature of 60° C. for 6 hours to obtain a nano copper oxide film;
[0100] S8-S9 are the same as S10-S11 in Example 2;
[0101] S10: Manually apply a thin silver paste on both ends of each nano copper electrode to draw out the electrode, and place it in a vacuum drying oven for heating and drying at a temperature of 60° C. for 4.5 h;
[0102] S11: The resistance of nano-copper after laser surface treatment at different copper oxide nanowire concentrations was measured using a desktop multimeter.
[0103] Figure 5 The resistance change of nano-copper after laser surface treatment at different copper oxide nanowire concentrations. It can be seen that as the content of copper oxide nanowires gradually increases, the content of nano-copper after laser photothermal reduction sintering increases, the resistance decreases, and the conductivity tends to saturation (the minimum is 0.66Ω / sq).
[0104] Embodiment 4:
[0105] S1: Weigh 0.5 g of polyvinyl pyrrolidone and 0.15 g of sodium formate, mix them in 3.0 mL of ethylene glycol and 1.0 mL of N,N-dimethylformamide solution, and heat and stir uniformly at 60 °C and 1200 rpm for 12 h to obtain a precursor solution;
[0106] S2 to S5 are the same as in Example 2;
[0107] S6: Take 7 pieces of polyphenylene sulfide special engineering plastic substrates with a thickness of 2 mm and a size of 20×50 mm, wash the surface impurities with isopropyl alcohol ultrasonic for 5 minutes, and dry them for later use;
[0108] S7-S8 are the same as in Example 1;
[0109] S9 is the same as S7 in Example 3;
[0110] S10 is the same as in Example 1;
[0111] S11: Draw a rectangular electrode pattern with a size of 36×6 mm, so that the laser sequentially performs pattern direct writing (laser direct writing induced passivation / photothermal reduction sintering) along the rectangular electrode pattern filling path at a power of 100 mW / 150 mW / 200 mW / 250 mW / 300 mW / 350 mW / 400 mW, maintaining a speed of 40 mm / s and a line scanning period of 35 μm, and converts the black nano copper oxide at the scanning path into red nano copper to obtain a nano copper electrode;
[0112] S12: Manually apply a thin silver paste on both ends of each nano copper electrode to draw out the electrode, and place it in a vacuum drying oven for heating and drying at a temperature of 60° C. for 6 hours;
[0113] S13: measuring the resistance of nano-copper after surface treatment with different laser powers by a desktop multimeter;
[0114] S14 is the same as S13 in Example 2;
[0115] S15: placing the nano copper electrode in a constant temperature blast drying oven, setting the temperature to 80° C., and recording the partial pressure change in real time through a data acquisition instrument;
[0116] S16 is the same as S15 in Example 2.
[0117] Figure 6 This is the optical image of nano copper when the laser power is 250mW. Figure 7 This is the optical image of nano copper when the laser power is 100mW. Figure 8 The optical image of nano copper when the laser power is 400mW. It can be seen that when the laser power is 250mW, the surface of the nano copper sintered by reduction is dense and flat, and the color is bright; when the laser power is small (100mW), the reduction threshold of nano copper is not reached, and the surface of nano copper is dark red and contains some copper oxide; and when the laser power is large (400mW), excessive energy injection will cause stress concentration in the surface area of nano copper, causing cracks.
[0118] Fig. 9 The figure shows the resistance change of nano-copper after surface treatment at different laser powers. It can be seen that as the laser power gradually increases, the energy per unit area of the focused spot increases, the photothermal effect is more significant, and the reduction sintering reaction is more complete. When the laser power is between 250 and 400 mW, the conductivity of the nano-copper electrode after surface treatment tends to saturation (the minimum is 0.36Ω / sq).
[0119] Fig.10 The relative resistance change of nano copper after surface treatment with different laser powers at 80°C over time. It can be seen that when the laser power is 250mW, the reaction temperature field and conditions of laser direct writing induced formate coordination passivation are the most reasonable. When the laser power increases or decreases, the high temperature and oxidation resistance of nano copper will decrease due to over-sintering (nano copper reoxidation) and insufficient reduction sintering (nano copper surface contains more copper oxides), and the relative resistance change in the same period will be greater.
[0120] Embodiment 5:
[0121] S1 to S10 are the same as those in Example 4;
[0122] S11: Draw a rectangular electrode pattern with a size of 36×6 mm, keep the laser power at 250 mW and the speed at 40 mm / s, and perform pattern direct writing (laser direct writing induced passivation / photothermal reduction sintering) along the rectangular electrode pattern filling path with a line scanning period of 15 μm / 20 μm / 25 μm / 30 μm / 35 μm / 40 μm / 45 μm in sequence, and convert the black nano copper oxide at the scanning path into red nano copper to obtain a nano copper electrode;
[0123] S12 is the same as in Example 4;
[0124] S13: measuring the resistance of nano copper after surface treatment at different laser line scanning cycles by a desktop multimeter;
[0125] S14 is the same as in Example 4;
[0126] S15: placing the nano copper electrode in a constant temperature blast drying oven, setting the temperature to 170° C., and recording the partial pressure change in real time through a data acquisition instrument;
[0127] S16 is the same as Example 4.
[0128] Figure 6 This is the optical image of nano-copper when the laser line scanning period is 35μm. Fig.11 This is the optical image of nano-copper when the laser line scanning period is 15μm. Fig.12 This is an optical image of nano-copper when the laser line scanning period is 45μm. It can be seen that when the laser line scanning period is 35μm, the period is close to the laser spot size, and the surface of the nano-copper after reduction sintering is relatively dense and flat; when the laser line scanning period is small (15μm), the overlapping area of the scanning path increases, resulting in increased heat accumulation and thermal stress in the repeated scanning area, causing cracks on the surface of the nano-copper; and when the laser line scanning period is large (45μm), a heat barrier appears between the scanning paths, which also causes fine cracks.
[0129] Fig.13 The resistance change of nano copper after surface treatment at different laser line scanning cycles shows that when the laser line scanning cycle is 35μm, the resistance of nano copper sintered by reduction is the lowest (0.36Ω / sq). As the laser line scanning cycle gradually decreases, the over-sintering caused by repeated heat accumulation will degrade the conductivity of nano copper. As the laser line scanning cycle gradually increases, the surface defects caused by the energy difference of photothermal reduction sintering between cycles will also affect the conductivity of nano copper.
[0130] Fig.14The relative resistance change of nano copper after treatment with different laser line scanning cycles at 170°C over time. It can be seen that when the laser line scanning cycle is 35μm, the nano copper after laser direct writing induced passivation has good high-temperature thermal stability. When the laser line scanning cycle decreases, the cracks caused by thermal stress will accelerate the infiltration of oxygen at high temperature, causing the oxidation resistance of nano copper to decrease. When the laser line scanning cycle increases, the barriers caused by the heat difference will lead to surface defects of nano copper, and the high-temperature oxidation resistance is also poor, and the relative resistance changes in the same period are greater.
[0131] Embodiment 6:
[0132] S1 to S5 are the same as in Example 4;
[0133] S6 to S10 are the same as in Example 1;
[0134] S11: Draw a rectangular electrode pattern with a size of 36×6 mm, so that the laser performs pattern direct writing (laser direct writing induced passivation / photothermal reduction sintering) along the rectangular electrode pattern filling path at a power of 250 mW, a speed of 40 mm / s, and a line scanning period of 35 μm, and converts the black nano copper oxide at the scanning path into red nano copper to obtain a nano copper electrode;
[0135] S12: Manually apply a thin silver paste on both ends of the nano copper electrode to draw out the electrode, and place it in a vacuum drying oven for heating and drying at 60°C for 2 hours;
[0136] S13: designing a voltage divider circuit board according to the resistance value of the nano copper electrode, connecting the nano copper electrode via an alligator clip wire, and connecting the data acquisition instrument via a Dupont wire;
[0137] S14: Weigh 0.5 g of polyvinyl pyrrolidone and mix it with 3.0 mL of ethylene glycol and 1.0 mL of N,N-dimethylformamide solution, and evenly heat and stir at 60° C. and 1200 rpm for 12 h to obtain a sodium formate-free precursor solution;
[0138] S15: Weigh 2.0 g of copper oxide nanowires (40 nm) and place them in a sodium formate-free precursor solution for full ultrasonic dispersion, with the ultrasonic real-time temperature being 55° C., the ultrasonic pulse width being 0.1 s, and the ultrasonic time being 3 min, to obtain a sodium formate-free nano copper oxide solution 1;
[0139] S16: Weigh 2.0 g of copper oxide nanowires (40 nm) and place them in the sodium formate-free nano copper oxide solution 1 for full ultrasonic dispersion, with the ultrasonic real-time temperature being 55° C., the ultrasonic pulse width being 0.1 s, and the ultrasonic time being 3 min, to obtain the sodium formate-free nano copper oxide solution 2;
[0140] S17: Weigh 1.0 g of copper oxide nanowires (40 nm) and place them in the sodium formate-free nano copper oxide solution 2 for full ultrasonic dispersion, with the ultrasonic real-time temperature being 55° C., the ultrasonic pulse width being 0.1 s, and the ultrasonic time being 2 min, to obtain a sodium formate-free nano copper oxide ink;
[0141] S18: Mechanically shake the sodium formate-free nano copper oxide ink for 2 minutes and let it stand for later use;
[0142] S19-S20 are the same as S6-S7 in Example 1;
[0143] S21: vacuum adsorb the polyphenylene sulfide special engineering plastic substrate on the spin coating chuck of the spin coater, and drop 1.5 mL of sodium formate-free nano copper oxide ink on the center of the substrate, and spin coat at 1000 rpm for 20 s and 500 rpm for 10 s;
[0144] S22: placing the polyphenylene sulfide special engineering plastic after spin coating with the sodium formate-free nano copper oxide ink in a constant temperature blast drying oven or a vacuum drying oven for heating and drying at a temperature of 60° C. for 2 hours to obtain a sodium formate-free nano copper oxide film;
[0145] S23: placing the polyphenylene sulfide special engineering plastic covered with the sodium formate-free nano copper oxide film on a laser processing platform with a 532nm wavelength continuous green light, and adjusting the height of the processing platform for laser focusing;
[0146] S24: Draw a rectangular electrode pattern with a size of 36×6 mm, so that the laser performs pattern direct writing (laser direct writing induced passivation / photothermal reduction sintering) along the rectangular electrode pattern filling path at a power of 250 mW, a speed of 40 mm / s, and a line scanning period of 35 μm, and converts the black nano copper oxide at the scanning path into red nano copper to obtain a sodium formate-free nano copper electrode;
[0147] S25: Manually apply a thin silver paste to both ends of the sodium formate-free nano-copper electrode to draw out the electrode, and place it in a vacuum drying oven for heating and drying at 60° C. for 2 h;
[0148] S26: designing a voltage divider circuit board according to the resistance value of the sodium formate-free nano-copper electrode, connecting the sodium formate-free nano-copper electrode via an alligator clip wire, and connecting the data acquisition instrument via a DuPont line;
[0149] S27: placing the nano copper electrode and the sodium formate-free nano copper electrode in a constant temperature blast drying oven, setting the temperature to 170° C., and recording the partial pressure change in real time through a data acquisition instrument;
[0150] S28: The data results are converted into relative resistance changes of the nano-copper electrode and the sodium formate-free nano-copper electrode through a voltage divider formula.
[0151] Fig.15 The relative resistance changes of nano copper (LIP-Cu) and nano copper (Cu) without sodium formate at 170°C over time. It can be seen that the high-temperature oxidation resistance of nano copper without sodium formate is far inferior to that of nano copper. Nano copper has better thermal stability at 170°C based on laser thermal induced formate coordination passivation protection.
[0152] Embodiment 7:
[0153] S1 to S26 are the same as in Example 6;
[0154] S27: placing the nano copper electrode and the sodium formate-free nano copper electrode in a constant temperature blast drying oven, setting the temperature to 120° C., and recording the partial pressure change in real time through a data acquisition instrument;
[0155] S28 is the same as in Example 6.
[0156] Fig.16 The relative resistance changes of nano copper (LIP-Cu) and nano copper (Cu) without sodium formate at 120°C over time. It can be seen that the conductivity of nano copper without sodium formate at 120°C continues to degrade, while the conductivity of nano copper remains stable within 105h without obvious degradation.
[0157] Embodiment 8:
[0158] S1 to S26 are the same as in Example 6;
[0159] S27: placing the nano copper electrode and the sodium formate-free nano copper electrode in a constant temperature blast drying oven, gradually raising the temperature from 30°C to 190°C, with an interval of 20°C, each temperature point lasting for 10 minutes, and recording the partial pressure change in real time through a data acquisition instrument;
[0160] S28 is the same as in Example 6.
[0161] Fig.17 The relative resistance changes of nano copper (LIP-Cu) and sodium formate-free nano copper (Cu) when the temperature gradually increases from 30°C to 170°C. It can be seen that the electrical performance degradation of sodium formate-free nano copper gradually accelerates during the step-by-step heating process, while the electrical performance of nano copper remains stable before the temperature rises to 150°C, and only slightly decreases when the temperature rises to 170°C.
[0162] The second aspect of the present invention proposes a full laser in-situ direct writing integrated sensor system, including a special engineering plastic rigid substrate, a high temperature resistant nano-copper interconnection circuit, a laser induced graphene temperature sensor, a voltage divider, an analog-to-digital converter (ADC), a microcontroller (MCU) and a low dropout linear regulator (LDO).
[0163] Embodiment 9:
[0164] S1: Adhere a PI tape with a width of 50 mm to the surface of a polyphenylene sulfide special engineering plastic substrate with a length of 60 mm, a width of 60 mm, and a thickness of 4 mm;
[0165] S2: Draw a circuit with an outer contour size of 45×27 mm, and use a 355nm wavelength ultraviolet nanosecond pulse laser to cut along the circuit contour;
[0166] S3: peeling off the PI tape within the cutting outline from the polyphenylene sulfide special engineering plastic substrate;
[0167] S4: taking an appropriate amount of the nano copper oxide ink prepared in Example 1, coating it on the polyphenylene sulfide special engineering plastic substrate, and heating and drying;
[0168] S5: peeling off the remaining PI tape from the polyphenylene sulfide special engineering plastic substrate to obtain the nano copper oxide film of the circuit outline;
[0169] S6: Using a 532nm continuous wavelength laser to perform laser direct writing induced passivation / photothermal reduction sintering along the circuit pattern filling path to obtain a high temperature resistant nano copper interconnect circuit;
[0170] S7: Design a temperature sensor of suitable size and shape, and use a 10.6 μm wavelength CO2 laser to induce in-situ carbonization at a corresponding position on the surface of the polyphenylene sulfide special engineering plastic substrate to form a laser-induced graphene temperature sensor;
[0171] S8: Connecting each component to the high temperature resistant nano-copper interconnection circuit through copper paste according to the circuit design, and heating and curing the copper paste;
[0172] S9: By connecting the data visualization serial port through an external DuPont line, the integrated temperature sensor system can be placed within the upper and lower temperature limits of the chip for temperature perception and measurement.
[0173] Fig.18 Optical photograph of the all-laser in-situ direct writing integrated sensor system.
Claims
1. A method for preparing high temperature resistant nano copper by laser direct writing, characterized in that: The steps include: (1) uniformly heating and stirring an alcohol solvent, an organic dispersant, an organic additive, and an appropriate amount of formate to obtain a precursor solution; (2) adding an appropriate amount of nano copper oxide to a precursor solution, and fully ultrasonically dispersing the nano copper oxide ink, wherein the nano copper oxide ink comprises: 43.0-50.4 wt% of nano copper oxide, 37.1-50.4 wt% of an alcohol solvent, 3.4-5.3 wt% of an organic dispersant, 0.0-9.5 wt% of an organic auxiliary agent, and 1.3-2.0 wt% of a formate; the nano copper oxide is copper oxide nanowires; (3) coating the nano copper oxide ink on the pretreated substrate, heating and drying, to obtain a nano copper oxide film; (4) The nano copper oxide film is subjected to one-step laser direct writing induced passivation / photothermal reduction sintering to obtain high temperature resistant nano copper, wherein the laser is a continuous green light with a wavelength of 532 nm, a power of 100 to 400 mW, a speed of 20 to 200 mm / s, and a scanning period of 20 to 40 μm. The induced passivation is to induce a passivation reaction of formate on the surface of the nano copper, so that the copper ions on the surface of the nano copper and the formate form a copper formate dimer complex to form an antioxidant coordination passivation layer.
2. The method for preparing high temperature resistant nano copper by laser direct writing according to claim 1, characterized in that: The alcohol solvent described in step (1) is at least one selected from monohydric alcohol and polyhydric alcohol.
3. The method for preparing high temperature resistant nano copper by laser direct writing according to claim 1, characterized in that: The organic dispersant in step (1) is selected from at least one of polyacrylamide organic polymers, polyethylene oxide organic polymers, tannin, and lignin.
4. The method for preparing high temperature resistant nano copper by laser direct writing according to claim 1, characterized in that: The organic auxiliary agent in step (1) is an organic amide selected from the group consisting of n H 2n+1 At least one of the alkylamides of NO (1≤n≤5).
5. The method for preparing high temperature resistant nano copper by laser direct writing according to claim 1, characterized in that: The formate described in step (1) is at least one selected from lithium formate, beryllium formate, sodium formate, magnesium formate, potassium formate, calcium formate, iron formate, manganese formate, cobalt formate, nickel formate, copper formate, zinc formate, barium formate and ammonium formate.
6. The method for preparing high temperature resistant nano copper by laser direct writing according to claim 1, characterized in that: The pretreatment described in step (3) is oxygen plasma surface treatment, and the treatment time is 60s to 150s.
7. The method for preparing high temperature resistant nano copper by laser direct writing according to claim 1, characterized in that: The temperature of the heating and stirring in step (1) is 50-70°C, the rotation speed is 600-1500 rpm, and the time is 2-20 hours; the real-time temperature of the ultrasonic dispersion in step (2) is 50-60°C, the ultrasonic pulse width is 0.1s, and the ultrasonic time is 0.1-2 hours; the temperature of the heating and drying in step (3) is 50-80°C, and the time is 2-12 hours.
8. A full laser in-situ direct writing integrated sensor system, characterized in that: The invention comprises a special engineering plastic substrate, a high temperature resistant nano copper interconnection circuit, a laser induced graphene temperature sensor, a voltage divider, an analog-to-digital converter (ADC), a microcontroller (MCU) and a low voltage drop linear regulator (LDO); the remaining parts are connected through the high temperature resistant nano copper interconnection circuit to realize the integrated sensor function, wherein the high temperature resistant nano copper interconnection circuit and the laser induced graphene temperature sensor are respectively formed in situ on the special engineering plastic substrate by using the full laser direct writing technology, and the high temperature resistant nano copper is prepared by the method described in any one of claims 1 to 7.
Citation Information
Patent Citations
A nano-copper-tin alloy conductive ink, its preparation method and application method
CN102675960B
Preparing method for copper-nickel alloy nano particles
CN105562701A
An antioxidant nano-copper solder paste, its preparation method and application
CN107267938B
A method for preparing antioxidant copper nanowires
CN107470609B
A method for preparing antioxidant micro / nano copper materials
CN109954876B